(untitled) (Bangladesh Journal of Pharmacology, 2014)
Traditionally Viola odorata is used for liver protection. To provide scientific support to its traditional use, aqueous methanolic extract of V. odorata (250 mg/kg and 500 mg/kg) was given to mice intoxicated with paracetamol. Obtained results demonstrated that the extract significantly (p<0.01-0.001) reduced paracetamol induced increase levels of serum hepatic enzymes and total bilirubin. Histopathological studies showed that the plant attenuated the hepatocellular necrosis and inflammation. HPLC results showed the presence of hepatoprotective flavonoids (isorhamnetin and luteolin) in the extract. It was concluded from the present study that V. odorata has hepatoprotective activity against paracetamol-induced liver injury in mice.